Research on the Stability of Express Delivery Supply Chain Based on Risk Propagation Model ------ Case Studies of SF Express and JD Logistics - Fan Yunhui (SHS Web of Conferences, 2025)
Against the backdrop of the rapid development of e-commerce, the stability of the express delivery supply chain, as a core component of the logistics system, has garnered increasing attention. Risk propagation is a critical factor affecting the stability of the express delivery supply chain. However, traditional research has largely been confined to qualitative descriptions of risks, lacking systematic quantitative analysis of risk propagation mechanisms. This study constructs a three-tier risk propagation model of “warehousing-transportation-distribution” based on complex network theory, analyzing the risk transmission characteristics of the express delivery supply chain from three dimensions: node risk propagation, path sensitivity, and system stability. Through a comparative analysis of SF Express (centralized network) and JD Logistics (distributed network), the following findings are revealed: (1) The risk amplification effect of centralized warehousing systems during peak order periods is 23% higher than the baseline value; (2) Crowdsourced delivery networks improve delivery flexibility while reducing terminal risks by 34%, but increase information leakage risks by 2.3 times. Based on the research results, optimization strategies such as dynamic path optimization algorithms and blockchain-based information isolation mechanisms are proposed, providing theoretical tools and practical references for risk prevention and control in the express delivery industry.